Traditional management of microorganisms in fermented beverages from cactus fruits in Mexico: an ethnobiological approach - César I. Ojeda-Linares; Mariana Vallejo; Patricia Lappe-Oliveras; Alejandro Casas (BMC, 2020)
Abstract Background Fermentation is an ancient technique for preserving and improving the qualities of food and beverages throughout the world. Microbial communities, not seen by the producers of fermented goods, are the actors involved in the fermentation process and are selected upon through different management processes in order to achieve a final product with culturally accepted features. This study documented the preparation of "colonche" which is a type of traditionally fermented beverages made with the fruits from several cactus species in two main producing regions of Mexico, the Altiplano and the Tehuacán Valley. We documented the selection processes of the cactus species used and the practices that could influence microbial community composition, as well as, how the producers reach the desirable sensorial attributes of the beverages. Methods We conducted 53 semi-structured interviews and participatory observations with colonche producers in 7 communities of the Altiplano and the Tehuacán Valley in order to characterize the practices and processes involved in the elaboration of the beverage. Opuntia and columnar cacti species used in colonche production were collected during fieldwork and identified. Selected sensorial attributes of Opuntia colonches were characterized by a ranking table and visualized by principal component analysis in order to distinguish differences of this beverage in the Altiplano localities. Results Thirteen cactus species are used for colonche production in both regions studied. In the Altiplano, the most commonly used fruit is Opuntia streptacantha because it contributes to the preferred attributes of the beverage in this region. Selection of substrates by producers depends on their preference and the availability of fruits of O. streptacantha and other species. Fermentation is mainly conducted in clay pots which is perceived to be the best type of vessel contributing to the preferred sensorial properties of colonche. The two main differences in colonche preparation between the villages are the practice of boiling the fruit juice and the use of pulque (fermented sap of Agave species) as inoculum. The most contrasting sensorial attributes selected between localities are the alcohol content and sweetness, which might be in accordance with the practices used for obtaining the final product. Colonche is produced mainly for direct consumption and secondarily used as a commercialized good to be sold for economic gains contributing to the general subsistence of households. The preparation methods are passed on by close relatives, mainly women. Conclusions Traditional producers of colonche use several techniques in order to reach specific sensorial attributes of the final product. The production of colonche has been upheld for generations but fermentation practices are divided into two categories; (1) the use of an inoculum (either from pulque, or from colonche saved from the previous year), and (2) the use of "spontaneous" fermentation. The differing practices documented reflect the contrasts in the preferred sensorial attributes between regions. Colonche is a beverage that contributes to regional pride, cultural identity and is appreciated because of its gastronomic value. Here, we argue that there is a clear relationship of human knowledge in the management of microbiota composition in order to produce this beverage. In-depth documentation of the microbiota composition and dynamics in colonche will contribute to the preservation of this valuable biocultural heritage.